Chitooligosaccharide accelerated wound healing in potato tubers by promoting the deposition of suberin polyphenols and lignin at wounds - Xie, Pengdong (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.